African American women with advanced‐stage ovarian cancer have worse outcomes regardless of treatment type. Issue 7 (July 2020) - Whitmore, Gabrielle; Ramzan, Amin; Sheeder, Jeanelle; Guntupalli, Saketh R
ABSTRACT : Objective : There has been an increase in the use of neoadjuvant chemotherapy in recent years. Our objective was to determine if African American women are more likely to receive neoadjuvant chemotherapy than primary debulking surgery, when compared to their Caucasian counterparts, and the impact of such an approach on oncologic outcomes. Methods : A retrospective cohort study was performed using the National Cancer Database (NCDB). Women aged 18‐90 years, diagnosed with stage IIIC or IV epithelial ovarian cancer between January 2010 through December 2014 were included. Women with unknown treatment or treatments outside of neoadjuvant chemotherapy or primary debulking surgery were excluded. Only women of Caucasian, African American, or Hispanic origin who received either neoadjuvant chemotherapy or primary debulking surgery were included; all other races were excluded. Descriptive statistics were computed, and continuous variables were assessed for normality. Groups were compared using ANOVA or non‐parametric medians tests for continuous variables, and chi‐squared tests were used for dichotomous or categorical variables. Logistic regression was used to identify predictors of treatment. A p value of 0.05 was considered statistically significant. Results : A total of 19 838 women with stage IIIC and IV epithelial ovarian cancer met the inclusion criteria. A total of 14 988 (75.6%) were treated with primary debulking surgery, while 4850 women (24.4%) were treated with neoadjuvant chemotherapy. Of those treated with neoadjuvant chemotherapy, 24.5% were white, 27.0% were African American, and 22.1% were Hispanic (p=0.005), and when adjusted for confounders, being African American was a predictor of receiving neoadjuvant chemotherapy (adjusted odds ratio (aOR) 1.29, 95% CI 1.10 to 1.51). Ninety‐day mortality rates were higher in African American women compared with Caucasian and Hispanic women (2.9% vs 2.0% vs 1.6%, p=0.013). There were no differences in 30‐day mortality, 90‐day mortality, or status at last contact in African American women, when comparing neoadjuvant chemotherapy and primary debulking surgery. In Caucasian women, outcomes were worse in women receiving neoadjuvant chemotherapy. Conclusions : Compared to other races, African American women with advanced ovarian cancer are more likely to receive neoadjuvant chemotherapy than primary debulking surgery and had a higher 90‐day mortality rate. In African American women there was no difference in outcomes based on treatment type.